2003
DOI: 10.1038/sj.bjc.6600955
|View full text |Cite
|
Sign up to set email alerts
|

Neural-cadherin expression associated with angiogenesis in non-small-cell lung cancer patients

Abstract: An immunohistochemical analysis for E(epithelial)-cadherin and N(neural)-cadherin expression in relation to tumour angiogenesis was performed in 150 patients with non-small-cell lung cancer (NSCLC). In all, 71 carcinomas (47.3%) were E-cadherin-negative. Epithelial-cadherin-negative tumours had lymph node metastases significantly more frequently than E-cadherin-positive tumours (P ¼ 0.0100). On the other hand, 46 carcinomas (30.7%) were N-cadherin-positive. Regarding tumour vascularity, there was no significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 34 publications
1
36
1
Order By: Relevance
“…It has been reported that the N-cadherin expression is uncommon in adenocarcinomas of the lung and is not a prognostic factor thereof (24,25). In the present study, incidences of N-cadherin expression were also low in poorly differentiated adenocarcinomas, as well as in epithelial and sarcomatous components of PCs.…”
Section: Discussionsupporting
confidence: 57%
“…It has been reported that the N-cadherin expression is uncommon in adenocarcinomas of the lung and is not a prognostic factor thereof (24,25). In the present study, incidences of N-cadherin expression were also low in poorly differentiated adenocarcinomas, as well as in epithelial and sarcomatous components of PCs.…”
Section: Discussionsupporting
confidence: 57%
“…Our previous studies revealed that tumour vascularity in NSCLCs is associated with intratumoral expression of VEGF-A (Masuya et al, 2001), interleukin-8 (Masuya et al, 2001, neuralcadherin (Nakashima et al, 2003), and that tumour vascularity is correlated with the survival rate of NSCLC patients (Nakashima et al, 2003). However, the present study did not show a correlation between the HGF/c-Met pathway and tumour vascularity in NSCLCs.…”
Section: Discussioncontrasting
confidence: 54%
“…Literature data demonstrated that N-cadherin is expressed during early neuroectoderm vascularization where it probably establishes interactions between neuroectoderm and endothelium, followed by a downregulation of N-cadherin in endothelia when the cells differentiate to a blood-retina and blood-brain barrier (Gerhardt et al, 1999). N-cadherin has also been indicated as an angiogenic factor in nonsmall-cell lung cancer because biopsies positive for N-cadherin were hypervascular (Nakashima et al, 2003). In our laboratory we could find that plasmin cleaved a 90 kD ectodomain fragment from N-cadherin, coined soluble N-cadherin.…”
Section: N-cadherin Function and Signallingmentioning
confidence: 99%